Gallbladder Agenesis in 17 Dogs: 2006–2016. (28th January 2018) - Sato, K.; Sakai, M.; Hayakawa, S.; Sakamoto, Y.; Kagawa, Y.; Kutara, K.; Teshima, K.; Asano, K.; Watari, T.
Abstract : Background: Gallbladder agenesis (GBA) is extremely rare in dogs. Hypothesis/Objectives: To describe the history, clinical signs, diagnosis, treatment, and outcomes of dogs with GBA. Animals: Seventeen client‐owned dogs with GBA. Methods: Medical records from 2006 through 2016 were retrospectively reviewed. Dogs were included when GBA was suspected on abdominal ultrasonography and confirmed by gross evaluation. Signalment, clinical signs, clinicopathological data, diagnostic imaging, histopathology, treatment, and outcome were recorded. Results: Dogs were of 6 different breeds, and Chihuahuas (10 of 17) were most common. Median age at presentation was 1.9 (range, 0.7–7.4) years. Clinical signs included vomiting (5 of 17), anorexia (2 of 17), ascites (2 of 17), diarrhea (1 of 17), lethargy (1 of 17), and seizures (1 of 17). All dogs had increased serum activity of at least 1 liver enzyme, most commonly alanine aminotransferase (15 of 17). Fifteen dogs underwent computed tomography (CT) cholangiography; common bile duct (CBD) dilatation was confirmed in 12, without evidence of bile duct obstruction. Gross evaluation confirmed malformation of the liver lobes in 14 of 17 dogs and acquired portosystemic collaterals in 5 of 17. Ductal plate malformation was confirmed histologically in 16 of 17 dogs. During follow‐up (range, 4–3, 379 days), 16 of 17 dogs remained alive. Conclusions and Clinical Importance: Dogs with GBA exhibit clinicopathological signs of hepatobiliary injury and hepatic histopathological changes consistent with a ductal plate abnormality. Computed tomography cholangiography was superior to ultrasound examination in identifying accompanying nonobstructive CBD distention. Computed tomography cholangiography combined with laparoscopic liver biopsy is the preferable approach to characterize the full disease spectrum accompanying GBA in dogs.